2023
DOI: 10.3390/app13042625
|View full text |Cite
|
Sign up to set email alerts
|

Joint Task Offloading, Resource Allocation, and Load-Balancing Optimization in Multi-UAV-Aided MEC Systems

Abstract: Due to their limited computation capabilities and battery life, Internet of Things (IoT) networks face significant challenges in executing delay-sensitive and computation-intensive mobile applications and services. Therefore, the Unmanned Aerial Vehicle (UAV) mobile edge computing (MEC) paradigm offers low latency communication, computation, and storage capabilities, which makes it an attractive way to mitigate these limitations by offloading them. Nevertheless, the majority of the offloading schemes let IoT d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Therefore, UAV deployment has become a key discussion issue in academia. In particular, a good UAV deployment can improve the quality and efficiency of task offloading for users and enhance the performance of the system [33,34]. Xu et al [35] proposed a sky-air-ground integrated mobile edge computing system to provide high-quality computing services in areas with missing or damaged communication infrastructures and designed an algorithm based on particle swarm optimization and greedy strategies to obtain a near-optimal solution for UAV deployment and mission offloading in the system.…”
Section: Uav-assisted Mec Networkmentioning
confidence: 99%
“…Therefore, UAV deployment has become a key discussion issue in academia. In particular, a good UAV deployment can improve the quality and efficiency of task offloading for users and enhance the performance of the system [33,34]. Xu et al [35] proposed a sky-air-ground integrated mobile edge computing system to provide high-quality computing services in areas with missing or damaged communication infrastructures and designed an algorithm based on particle swarm optimization and greedy strategies to obtain a near-optimal solution for UAV deployment and mission offloading in the system.…”
Section: Uav-assisted Mec Networkmentioning
confidence: 99%
“…Machine learning-based task allocation [28] DQN-D EC [54] IoT [38] MARL IoT [42] ACO IoT, 5G [51] FLOM-Opt [53] Q-Learning IoT, IoV [57] MA IoT [58] Heuristic, RL EC Quality of service task allocation [26] EC [32] MMAS EC [48] QT EC, IoT Resource-aware task allocation [76] MAPPO MEC [62] MDP EC [14] MAP VEC [75] JTORA VEC [72] JTORA MEC [74] JTORA MEC [15] DNF [16] MARL MEC [21] JTORA NOMA-MEC [37] EC [39] ELB [40] Knapsack MCS [70] EC, 5G…”
Section: Proposed Task Allocation Optimization (Rq2) Applied Network ...mentioning
confidence: 99%
“…Chen et al [7] presented a UT-UDN system model that demonstrated a 20% reduction in time delay and a 30% decrease in energy costs, as indicated by simulation results. Elgendy et al [8] proposed a Mobile Edge Computing solution for Unmanned Aerial Vehicles (UAVs), which uses a multi-layer resource allocation scheme, a load balancing algorithm, and integer programming to achieve cost reduction. In the context of multi-cloud spatial crowdsourcing data placement, Wang et al [9] introduced a data placement strategy with a focus on cost-effectiveness and minimal latency.…”
Section: Related Workmentioning
confidence: 99%